Mercury Content in Dietary Supplements From Poland Containing Ingredients of Plant Origin: A Safety Assessment - Puścion-Jakubik, Anna; Mielech, Anita; Abramiuk, Dominika; Iwaniuk, Małgorzata; Grabia, Monika; Bielecka, Joanna; Markiewicz-Żukowska, Renata; Socha, Katarzyna (Frontiers in Pharmacology, 2021)
Mercury (Hg) is a fairly common environmental pollutant. Chronic exposure to this element may cause, inter alia, kidney damage and disturbances in the functioning of the nervous system. Literature data indicate that food, including dietary supplements (DS), maybe sometimes contaminated with Hg. Therefore, the aim of the study was to assess Hg content in DS containing ingredients of plant origin. The study covered 200 DS available for sale in Poland. Hg content was determined by AAS method with the amalgamation technique using the AMA-254 analyzer. The highest average Hg content was found in preparations used as adjuncts for lowering glucose levels (23.97 ± 38.56 µg/kg). The highest percentage of PTWI (1.143%) was found in DS aimed at improving vitality. Due to the fact that DS are commonly used, their quality should be constantly monitored.